Evaluation of 2D ion chamber arrays for patient specific quality assurance using a static phantom at a 0.35T MR-Linac - Renkamp, Claudia Katharina; Eulenstein, Daniela; Sebald, Moritz; Schlüter, Fabian; Buchele, Carolin; Rippke, Carolin; Debus, Jürgen; Klüter, Sebastian (Zeitschrift für medizinische Physik, 2025)
Introduction - Patient specific quality assurance (QA) in MR-Linacs can be performed with MR-compatible ion chamber arrays. However, the presence of a static magnetic field can alter the angular response of such arrays substantially. This works investigates the suitability of two ion chamber arrays, an air-filled and a liquid-filled array, for patient specific QA at a 0.35T MR-Linac using a static phantom. - Methods - In order to study the angular response, the two arrays were placed in a static, solid phantom and irradiated with 9.96×9.96cm2 fields every 10° beam angle at a 0.35T MR-Linac. Measurements were compared to the TPS calculated dose in terms of gamma passing rate and relative dose to the central chamber. 20 patient specific quality assurance plans were measured using the liquid-filled array. - Results - The air-filled array showed asymmetric angular response changes of central chamber dose of up to 18% and down to local 3mm/3% gamma rates of 20%, while only minor differences within 3% (excluding parallel irradiation and beams through the couch edges) were found for the liquid-filled ion chamber array without rotating the phantom. Patient plan QA using the liquid-filled array yielded a median local 3mm/3% 3D gamma passing rate of 99.8% (range 96.9%-100%). - Conclusion - A liquid-filled ionization chamber array in combination with a static phantom can be used for efficient patient specific plan QA in a single measurement set-up in a 0.35T MR-Linac, while the air-filled ion chamber array phantom shows large angular response changes and has its limitations regarding patient specific QA measurements.